2021
DOI: 10.3390/jmse9091028
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Sensitivity of Moored and Articulated Multibody Offshore Structures in Waves

Abstract: Within the framework of Space@Sea project, an articulated modular floating structurewas developed to serve as building blocks for artificial islands. The modularity was one of the keyelements, intended to provide the desired flexibility of additional deck space at sea. Consequently, the layout of a modular floating concept may change, depending on its functionality and environmental condition. Employing a potential-flow-based numerical model (i.e., weakly nonlinear Green function solver AQWA), this paper studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…This is because the properties of the floating module, as well as its superstructures may be different from one to another. Combining our previous studies (Jiang, 2021;Jiang et al, 2021;Jiang et al, 2022a;Jiang et al, 2022b;Jiang and el Moctar, 2023), the procedure of defining the limiting criteria of a module floating concept may be summarized as follows: I. Prepare the geometry and the structural properties of the design module, including mass, center of gravity, moments of inertia, connectors, mooring system, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the properties of the floating module, as well as its superstructures may be different from one to another. Combining our previous studies (Jiang, 2021;Jiang et al, 2021;Jiang et al, 2022a;Jiang et al, 2022b;Jiang and el Moctar, 2023), the procedure of defining the limiting criteria of a module floating concept may be summarized as follows: I. Prepare the geometry and the structural properties of the design module, including mass, center of gravity, moments of inertia, connectors, mooring system, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Determine the optimal number of modules and configurations. One can reference to Jiang et al (2021), which studies the hydrodynamic sensitivity of multimodule structures. III.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our review of research on MFSs, it becomes evident that the potential flow theory approach has been widely utilized. In these studies, connections are conventionally modeled as independent linear springs with six degrees of freedom [8]. For instance, Jiang et al [9] assessed the potential flow theory solver's ability to simulate an articulated and moored floating system consisting of multiple bodies.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this background, a number of studies on the MFS have been developed [9,10]. Among these, Jiang et al [11] investigated the effect of module arrangement on the hydrodynamic sensitivity of the MFS. Results revealed that the hydrodynamic responses were similar in chain-type and parallel-type, and the motion responses of the first up-wave module were the largest.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed novel MFS system is initially designed for a representative sea zone with the well-shielded effect of the natural surrounding islands in the South China Sea. Compared with the current general MFS [11,13], the integration of floating artificial reefs can provide habitats for marine species, thereby improving the marine ecological environment around the MFS system. The outermost floating artificial reef modules coupled with WECs can attenuate the wave loads, as well as producing considerable wave energy.…”
Section: Introductionmentioning
confidence: 99%